Effect of Irrigation Method and Compost Type on the Growth and Yield of Broad Bean (Vicia faba L.) - talal hussin, talal; Talib Eghap Hussin, Talib Eghap Hussin; Qasim Badr Idress, Qasim Badr Idress (University of Thi-Qar Journal of agricultural research, 2025)
A field experiment was became performed at the College of Agriculture and Marshlands, University of Thi-Qar, 2022-2023, to study the consequences of irrigation methods (surface irrigation and basin irrigation) and compost kind (local and imported) soil properties consisting of (bulk density, moisture content, field capacity and mean weighted diameter) and growth indicators (plant height, number of branches per plant, leaf area, number of leaves per plant, and dry weight of plant) as well as the yield of broad beans (number of pods per plant, number of seeds pod, weight of 100 seeds, plant yield, and total seed yield). The experiment was conducted according to a split-plot system in a randomized complete block design, with main plots representing irrigation methods and subplots representing compost types, in triplicate, resulting in a total of 18 experimental units. Least significant differences (L.S.D) at the 0.05 probability level were used to compare treatments. The results showed that basin irrigation outperformed surface irrigation, and local compost was superior to imported compost in improving physical soil properties by reducing bulk density, increasing moisture content and field capacity and mean weighted diameter. Additionally, both the growth indicators and yield were significantly improved by increasing plant height, number of branches per plant, leaf area, number of leaves per plant, dry weight of the vegetative part per plant, number of pods per plant, number of seeds per pod, weight of 100 seeds, individual plant yield, and total seed yield.